Consolidated Financial Statements - Elements of the Management Decision to Invest - Cristina Ioana Antik (Agora International Journal of Economical Sciences (AIJES), 2017)
The objective of the consolidated financial statements is to present the financial position, performance and evolution of the financial position in relation to the units included in the group of companies, as if it were a single company. The subject of consolidation is the companies within the group, and the object of consolidation is their annual financial statements. Consolidation of financial statements is a technique of engineering financial accounting, which aims to produce information necessary for external users. It is also a management tool, as it allows to clarify the complex relations between subsidiaries and the parent company and to compare the results obtained with the set objectives.
Keywords: 330